Aplikasi Manajemen Kontrol Dokumen Pada PT. Siantar Top, Tbk Bekasi Menggunakan Metode Waterfall - Rahayu Ningsih; Riris Lestiowati; Minda Septiani; Ulfa Dwiyanti (LPPM Universitas Bina Sarana Informatika, 2019)
In the current era of globalization, information technology is advancing rapidly, and computers are equipment to facilitate human work at this time. At PT. Siantar Top, Tbk to get ISO 9001: 2015 certification, one of which is the document control system. But there are still many using archives manually so that it takes a long time in the search and has less effective and inefficient impact. This document is for large organizations / companies that have dozens of departments with constraints in the process which is very inconvenient for the part responsible for control documents. This application is built web-based with PHP as the programming language. The design of the model uses LRS and ERD and uses the waterfall method. So that this application helps in terms of managing and searching document data when needed does not take long. Computerized data storage makes it easier to store data stored neatly in the database and reduces risks associated with data loss and data damage.